Hand-held dynamometry for assessment of muscle strength in patients with inflammatory myopathies. (7th October 2020) - Saygin, Didem; Oddis, Chester V; Moghadam-Kia, Siamak; Rockette-Wagner, Bonny; Neiman, Nicole; Koontz, Diane; Aggarwal, Rohit
Abstract: Objectives: Muscle weakness in idiopathic inflammatory myopathies (IIMs) is conventionally assessed using manual muscle testing (MMT). However, more objective tools must be developed to accurately and reliably quantify muscle strength in myositis patients. Hand-held dynamometry (HHD) is a quantitative, portable device with reported reliability in neuromuscular disorders. Our aim was to assess the reliability, validity and responsiveness of HHD in myositis. Methods: Myositis patients [DM, necrotizing myopathy (NM), PM and anti-synthetase syndrome] evaluated at the University of Pittsburgh myositis centre were prospectively enrolled. Each patient was assessed at 0, 3 and 6 months for validated outcome measures of myositis disease activity and physical function. At each visit, muscle strength was assessed using both MMT and HHD (Micro FET2, Hoggan Health Industries, Draper, UT, USA). The reliability, validity and responsiveness of the HHD was assessed using standard statistical methods. Results: Fifty IIM patients (60% female; mean age 51.6 years; 6 PM, 9 NM, 24 DM and 11 anti-synthetase syndrome) were enrolled. HHD showed strong test–retest intrarater reliability ( r = 0.96) and interrater reliability ( r = 0.98). HHD correlated significantly with the MMT score ( r = 0.48, P = 0.0006) and myositis disease activity and functional measures. Longitudinal analysis showed a significant and strong association between the HHD and MMT as well as 2016 ACR/EULAR myositis response criteria ( r = 0.8, P < 0.0001) demonstrating responsiveness. The mean effect size and standardized response mean of HHD was large: 0.95 and 1.03, respectively. MMT had a high ceiling effect compared with HHD. Conclusion: HHD demonstrated strong reliability, construct validity and responsiveness in myositis patients. External validation studies are required to confirm these findings.